THE DISINHERITED DRAMATIST ON THE RECEPTION OF VYNNYČENKO’S PLAYS IN GERMANY - Rudnytzky, L. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article researches into the connection of Volodymyr Vynnyčenko’s dramaturgic creative work and the German-speaking cultural space on the rich archival material. It proves that the plays by the Ukrainian author organically fitted in German expressionists’ literary-artistic searches, were often performed on the stages of Berlin, Munich, Nuremberg, as well as of Vienna and Salzburg, their reception by Western European critics and viewers is analysed. Simultaneously, it points out that such reception of the Ukrainian author’s creative work also depended on Volodymyr Vynnyčenko’s very personality, who was first and foremost known in the West as a politician and social activist of Ukraine.